Efficacy of Prefabrications on Constructions' Waste Cost and its Eco-Efficiency - Alireza, Mirjalili (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Prefabrication in construction industry can probably reduce the cost of waste. In this research, the advantages and disadvantages of prefabrication and its eco-efficiency were identified; then the development strategies of this industry were reviewed. For this purpose, the questionnaires were used to select the proper sub-systems for prefabrication.
Keywords: prefabrication; construction waste; costs; eco-efficiency; high-rise buildings; prefabrykacja; odpady budowlane; koszty; ekoefektywność; budynek wysokościowy